A mountain of millipedes X: Species of Pyrgodesmidae and Cryptodesmidae in the Udzungwa Mountains, Tanzania (Diplopoda, Polydesmida) - Enghoff, Henrik (European Journal of Taxonomy, 2022)
Three new species of the family Pyrgodesmidae Silvestri, 1896 from the Udzungwa Mountains are described: Cryptocorypha geminiramus sp. nov., Cryptocorypha cactifer sp. nov., and Cryptocorypha exovo sp. nov. Several additional, unidentifiable pyrgodesmids from the Udzungwa Mountains are recorded. Elythesmus enghoffi Hoffman, 1978 (Cryptodesmidae Karsch, 1880), is recorded from the East Usambara (type locality), West Usambara, Uluguru, Nguru (Kanga) and Udzungwa Mountains, and its variation in size and body ring numbers is analyzed. The surface sculpture of pro- and metazonites is discussed.